ANALISIS MOTIVASI KERJA DAN KEPEMIMPINAN ISLAMI DALAM MENINGKATKAN KINERJA KARYAWAN PADA CV. INDONESIA 100 PUBLISHING - Mohammad Irfani (Jurnal Studi Islam dan Sosial, 2021)
Analysis of Work Motivation and Islamic Leadership in Improving Employee Performance at Cv. Indonesia 100 Publishing. The purpose of this study are, First to determine work motivation in improving employee performance. Second, to find out Islamic leadership in improving employee performance. Third, to determine work motivation and Islamic leadership in improving employee performance. With the results of research work motivation and Islamic leadership in improving employee performance if supported by several conditions: First, understand the basic process of motivation, needs models, action objectives and the influence of experience and expectations. Second, knowing the factors that renew motivation, the pattern of needs that drive towards the target and the circumstances in which these needs are met or not met. Third, Knowing that motivation cannot be achieved simply by creating a state of complacency can lead to complacency and weakness. Fourth, leadership is a one-way or reciprocal influence process to achieve obedience. Fifth, Islamic leadership can touch from various aspects of life such as how to make friends in companies, live in companies according to Islamic sharia and live as a state. Sixth, employee performance goals are a specific statement that explains the results that must be achieved, when and by whom the targets to be achieved are completed. Seventh, performance standards explain what managers expect from workers so that employees must understand them. Performance standards are the yardstick against which performance is measured to be effective.